Early Growth of the Star Formation Rate Function in the Epoch of Reionization: An Approach with Rest-frame Optical Emissions - Yoshihisa Asada; Kouji Ohta (The Astrophysical Journal, 2024)
We present a star formation rate function (SFRF) at z ∼ 6 based on star formation rates (SFRs) derived by spectral energy distribution fitting on data from rest-frame UV to optical wavelengths of galaxies in the CANDELS GOODS-South and North fields. The resulting SFRF shows an excess compared to the previous estimations by using rest-frame UV luminosity functions (LFs) corrected for the dust attenuation and is comparable to that estimated from a far-infrared LF. This suggests that the number density of dust-obscured intensively star-forming galaxies at z ∼ 6 has been underestimated in the previous approach based only on rest-frame UV observations. We parameterize the SFRF using the Schechter function and obtain the best-fit parameter of the characteristic SFR (SFR*) when the faint-end slope and characteristic number density are fixed. The best-fit SFR* at z ∼ 6 is comparable to that at z ∼ 2, when the cosmic star formation activity reaches its peak. Together with SFRF estimations with a similar approach using rest-frame UV to optical data, the SFR* is roughly constant from z ∼ 2 to ∼6 and may decrease above z ∼ 6. Since the SFR* is sensitive to the high-SFR end of the SFRF, this evolution of SFR* suggests that the high-SFR end of the SFRF grows rapidly during the epoch of reionization and reaches a similar level observed at z ∼ 2.